A capacitação dos professores da escola básica do município de Cruz a partir da coleção "Educação musical". - Silva, Francisco Baltar da (2018)
This research, carried out in six public schools in the City of Cruz - CE, presents the contributions of the continuous training in Arts, in the practice of the generalist teachers in the classroom and in the implantation of the musical content within the Arts class in the school curriculum. The general objective of this research is to investigate the teachers’ qualification in initial series of Elementary School, based on the contribution of the Musical Education Collection, in the implementation of the musical content within the Art discipline in the curriculum of the public schools of the City of Cruz - CE. It seeks to confirm the theory that continuing education is a fundamental tool so that pedagogues can to experiment and live the arts, as well as be able to safely teach this discipline in the school context and assist in returning it to the school curriculum. The Collection that was used as support in this training is composed of books with classes of theoretical and practical arts, with pedagogical resources and accessible musical instruments, with the objective of also being used as a tool for the training of multitudinous teachers. The methodology used was the qualitative data collection, carried out during the year 2018, through two questionnaires with twelve teachers. The theoretical basis of this research was the collaboration of many authors and Laws that have guided and are currently helping Music Education in our country: Maura Penna, Sergio Figueiredo, Claúdia Bellochio, among others; and Laws 11,769 / 2008 and 13,278 / 2016. Finally, from the perspective of these pedagogues, we gather the information of this formation in the musicalization and practice of the musical instruments offered, first in their lives, then in their classroom work with their students, and in the implantation of music within the discipline in the school curriculum. We also investigate with current teachers whether these formations and use of didactic material continued in the years after the training.